The Effectiveness of Using English Songs Toward Students' Vocabulary Mastery at Class X of SMK Negeri 2 Gerung in Academic Year 2022/2023 - Arantiya Putri Ananda; Ni Wayan Mira Susanti; Husnul Lail; Eka Fitriana (Jurnal Ilmiah Profesi Pendidikan, 2023)
English vocabulary is crucial for students' language proficiency in reading, speaking, listening, and writing. To increase vocabulary, teachers can use effective techniques, such as incorporating English songs into the curriculum. This research aims to assess the impact of using songs for vocabulary instruction on 40 students from SMK Negeri 2 Gerung. They were split into an experimental class (X-TEI) exposed to English songs and a control class (X-TOI) using flashcards.After the treatment, post-test scores showed significant differences between the two classes. The experimental class scored 80.25, while the control class scored 66.75. Data analysis in SPSS demonstrated a substantial difference in vocabulary mastery (sig 2-tailed < 0.05) between the two groups. Hypothesis testing confirmed the acceptance of the alternative hypothesis (Ha) and rejection of the Null Hypothesis (Ho). In conclusion, incorporating English songs effectively improved students' vocabulary mastery in class X at SMK Negeri 2 Gerung during the academic year 2022-2023.